Enhancing the stability of environmental resistance of alloyed CdZnSeS@ZnS quantum dots by doping Ti ions into shell layer. (10th December 2022) - Fang, Fan; Liu, Haochen; Wen, Zuoliang; Liu, Chenxi; Xu, Bing; Zhang, Zhikuan; Wang, Kai; Ertugrul, Mehmet; Lei, Wei; Sun, Xiao Wei
Abstract: Colloidal quantum dots (QDs) are promising luminescent materials for display and lighting, but their stability has long been an issue. Here, we designed a passivation strategy of doping Ti ions into the shell of alloyed CdZnSeS@ZnS QDs. The results showed that Ti ions were successfully doped into the ZnS shell and the stability of QDs was improved. In the aging test, the Ti ions doped QDs maintained 51.4% of the initial performance after 90 h of aging, while the pristine QDs decreased to less than 25% of the initial value. In addition, we discuss the reasons why Ti ions doping improves the stability of QDs. Ti ions are found to form Ti–S bonds in the ZnS shell, which has high binding energy and strong oxidation resistance. Most importantly, since there is no external physical insulating coating, the optimized QDs can also be directly used in electroluminescent devices, showing great potential in electroluminescence applications.